Borboletas Amarelas: a presença dos alunos Xakriabá no IF Goiano - Campus Urutaí - Almeida, Ranna Iara de Pinho Chaves (2019)
This essay is a reflection about the presence of the Xakriabá indian students at the Instituto Federal Goiano - Campus Urutaí/GO, searching to identify the motivations and the network of relationship mobilized by these ethnic young ones to adapt to the scholar culture and the institutional diurnal, as well as the perception and the significance to the others non-indians institutional personnel. The Xakriabás are a Jê people that live on the middle region of São Francisco river, at São João das Missões city, on the north of the Minas Gerais state. The Instituto Federal Goiano - Campus Urutaí is an educational institute established by the Law no. 1.923 in the southeast of Goiás. This essay seeks to trace the main aspects that outlines the dinamics of the Xakriabá at the IF Goiano - Campus Urutaí focusing on the contact among the indians versus non-indians. Therefore, the focus was on the dinamics established by these students and their relational network at the campus and also on the family project mobilized so these students could go to school